2021
DOI: 10.3390/pharmaceutics13050612
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical CO2 Extraction of Organic Solvents from Flunisolide and Fluticasone Propionate

Abstract: In this work, Class 2 and Class 3 solvents contained in two corticosteroids, flunisolide (Fluni) and fluticasone propionate (Fluti), were reduced to a few ppm by supercritical CO2 extraction. The process was carried out at pressures from 80 to 200 bar, temperatures of 40 °C and 80 °C, and at a fixed CO2 flow rate of 0.7 kg/h. The results demonstrated that CO2 density is the key parameter influencing the extraction kinetics and the solvent final residue. In particular, in the range investigated, optimal pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Like CAPE, ARC also activated tumor suppressor activity in p53 by abrogating its complex with mortalin [ 33 ]. Several studies have demonstrated the supercritical extraction that uses high pressure, low temperature, and allows reduction in organic solvents as a preferred method of extraction for retaining sensitive natural bioactive compounds [ 34 , 35 ]. Supercritical extracts have been shown to retain aroma as well as bioactive profile that closely resembles the original source [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Like CAPE, ARC also activated tumor suppressor activity in p53 by abrogating its complex with mortalin [ 33 ]. Several studies have demonstrated the supercritical extraction that uses high pressure, low temperature, and allows reduction in organic solvents as a preferred method of extraction for retaining sensitive natural bioactive compounds [ 34 , 35 ]. Supercritical extracts have been shown to retain aroma as well as bioactive profile that closely resembles the original source [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…scCO 2 is a commonly used extractant in the pharmaceutical and natural products industries [69][70][71][72][73]. It is a non-toxic, non-flammable, and environmentally friendly solvent [74,75], and it can be easily removed by depressurization and evaporation [76][77][78]. The extracts were obtained with scCO 2 at 50 • C under 2000 (a) and 6000 PSI (b) (Table 3).…”
Section: Extractionmentioning
confidence: 99%